2014
DOI: 10.1073/pnas.1419497111
|View full text |Cite
|
Sign up to set email alerts
|

Selective degeneration of a physiological subtype of spinal motor neuron in mice with SOD1-linked ALS

Abstract: Amyotrophic lateral sclerosis (ALS; Lou Gehrig's disease) affects motor neurons (MNs) in the brain and spinal cord. Understanding the pathophysiology of this condition seems crucial for therapeutic design, yet few electrophysiological studies in actively degenerating animal models have been reported. Here, we report a novel preparation of acute slices from adult mouse spinal cord, allowing visualized whole cell patch-clamp recordings of fluorescent lumbar MN cell bodies from ChAT-eGFP or superoxide dismutase 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
58
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 59 publications
(61 citation statements)
references
References 36 publications
(40 reference statements)
2
58
1
Order By: Relevance
“…Thus, we were unable to directly correlate the reduction or absence of aggregates at 3 mo of age with the greatest prolongation of survival. [Note that the presence of aggregates in ventral horn motor neurons of G85R SOD1YFP mice is prominent between 1 and 3 mo of age but then is substantially reduced thereafter (19)]. However, our observation from six double transgenic animals killed at 2.5 mo of age for morphology analysis was that two animals of the six exhibited strikingly low levels of aggregate formation.…”
Section: Discussionmentioning
(Expert classified)
See 1 more Smart Citation
“…Thus, we were unable to directly correlate the reduction or absence of aggregates at 3 mo of age with the greatest prolongation of survival. [Note that the presence of aggregates in ventral horn motor neurons of G85R SOD1YFP mice is prominent between 1 and 3 mo of age but then is substantially reduced thereafter (19)]. However, our observation from six double transgenic animals killed at 2.5 mo of age for morphology analysis was that two animals of the six exhibited strikingly low levels of aggregate formation.…”
Section: Discussionmentioning
(Expert classified)
“…The transgenic G85R SOD1YFP strain (containing greater than 210 copies of the transgene via homozygosity, referred to as the 737 line) has been described (14). By 3-4 mo of age, hind-limb clenching and rotarod dysfunction is observed (19), and lower extremity paralysis develops by 6.5 mo of age. The strain transgenic for Thy1-human Hsp110 (HspA4L) was produced by injecting B6/SJL zygotes (Yale Transgenic Mouse Service) with a construct described in SI Methods.…”
Section: Methodsmentioning
confidence: 99%
“…This reflects extensive reduction of functional motor units and is morphologically correlated with loss of MNs in the lateral TA/GC motor pool (8), loss of axons in lumbar ventral nerve roots (Fig. 2B, Left), reduced gastrocnemius muscle fiber area (Fig.…”
Section: −4mentioning
confidence: 91%
“…The development of clinical symptomslower extremity tremor, twitchiness or clenching, or reduced performance on the rotarod-is associated with MN loss, presumed to involve the MNs that innervate fast-twitch muscle. In a G85R SOD1YFP model of SOD1-linked ALS mice, which become paralyzed by 6 mo of age, we observed that development of such clinical symptoms by 4 mo corresponds to selective loss of lowresistance, fast-firing MNs in acute spinal cord slices prepared from these mice (8). The resulting lack of fast-firing physiology in the context of an in vitro preparation led us to ask: How does the intact G85R SOD1YFP motor system perform motor tasks after selective cell loss in the context of symptomatic degeneration?…”
mentioning
confidence: 86%
See 1 more Smart Citation